Az 1843/44. évi országgyűlés a liberális főrendi ellenzék szemszögéből - Deák Ádám (Móra Akadémia, 2018)
The Diet in 1839/40 was successful, because the Diet created 51 laws which the king approved. Lajos Batthyány led the liberal lords party, which contributed the success. Then they made great hopes the next Diet which Ferdinand V. (1835– 1848) convened on 14 May 1843. The king recommended lot of reform measures, therefore the mood was optimistic. However the liberal lords were disappointed, because the conservative members sent back lot of laws proposed for the House of Commons that they slow down the job. More liberal lords said the disappointment for example Earl József Pálffy, who wanted to abolish the House of Lords. The Diet in 1843/44 was unsuccessful for the liberal politicians, bacause the king accepted just 13 laws. However this Diet was important for the liberal lords, because they developed and united, later they founded the Opposition Party in 1847.